Traditional Chinese medicine monomers: a new strategy against diabetic kidney disease by regulating cholesterol efflux - Wu, Chenguang; Sun, Jianing; Shi, Junwei; Li, Zhe; An, Yan; Zhu, Han; Wang, Lifan; Liu, Peng (Frontiers in Nutrition, 2025)
Diabetic kidney disease (DKD), a prevalent microvascular complication of diabetes, is driven by a complex pathogenesis. A key pathological hallmark of early DKD is intrarenal lipid deposition, a process pivotally driven by impaired cholesterol efflux. This efflux is critically mediated by ATP-binding cassette (ABC) transporters, primarily ABCA1 and ABCG1. Dysfunction of these transporters precipitates cholesterol accumulation in renal cells, subsequently inducing oxidative stress, inflammation, and fibrosis. Recently, a diverse range of herbal monomers has emerged as a promising class of therapeutic agents for DKD. Compounds—including Anthocyanins, Morroniside, Resveratrol, Tanshinone, Puerarin, Baicalin, Curcumin, Protocatechuic acid, and Kaempferol—have been shown to activate the PPARγ and LXRα signaling pathways. This activation upregulates the expression of ABCA1 and ABCG1, thereby enhancing cholesterol efflux, mitigating renal lipid deposition, and ultimately slowing DKD progression. However, this body of research is largely limited to preclinical studies in vitro and in animal models. Consequently, the complex, multi-target mechanisms of these compounds in vivo remain poorly understood. Future investigations should therefore leverage multi-omics technologies to comprehensively delineate these mechanisms. Furthermore, large-scale clinical trials are imperative to validate the therapeutic efficacy and safety of these agents, potentially establishing novel strategies for the prevention and treatment of DKD.